Business Process Improvement Design for Academic Administration in Supporting the Achievement of Timely Graduates in the Master of Management Study Program at the University of North Sumatra - Wibowo, Azharie; Sembiring, Meilita Tryana; Sinulingga, Emerson Pascawira (Institute of Computer Science (IOCS), 2024)
This research is based on data on the number of on-time graduates of Prodi MM USU not proportional to the number of active students of Prodi MM USU, still below 50%. The purpose of this research is to identify the current business processes of Prodi MM USU, find out the main causes of the less-than-optimal number of on-time graduates, find recommendations for technical solutions and recommendations for the flow of academic administration business processes, and to see the time efficiency between the current business process and the recommended business process. The business process modelling of MM USU study programme is done with BPMN. Analysis of the factors causing students to graduate not on time was carried out using the discussion and interview method, then analysed with Root Cause Analysis with the 5WH + 1 H method, then formulated technical solutions and recommendations for business process improvement using the Value-Added Assessment (VAA) method. Some technical solutions or recommendations for improvement in business processes are increasing the number of administrative staff personnel proportional to the increase in the number of students, building a supervision system as a monitor and reminder of research limits that have been carried out by students and supervisors. The time analysis conducted obtained time efficiency results of 30.6% in the colloquium seminar process, 10.5% in the results seminar or company seminar process and 12.5% in the thesis examination process.